Thermal distribution in amorphous InSnZnO thin‐film transistor. Issue 11 (18th October 2013) - Urakawa, Satoshi; Tomai, Shigekazu; Ueoka, Yoshihiro; Yamazaki, Haruka; Kasami, Masashi; Yano, Koki; Wang, Dapeng; Furuta, Mamoru; Horita, Masahiro; Ishikawa, Yasuaki; Uraoka, Yukiharu; Yamaguchi, Hiroshi; et al.
Abstract We have investigated thermal distribution of an amorphous InSnZnO thin‐film transistor (TFT) under voltage stress by using thermal imaging system. To clarify an influence of only self‐heating phenomenon on reliability, we have focused on a channel scale dependence of heating. As the result, heating effect were strongly depended on channel scale and showed two types of dependences on channel length and width. When positive bias stress was applied to TFT, severe threshold voltage shift and high heating temperature were observed for wider TFT. Moreover, reliability under voltage stress was seems to be affected by accumulation of heating in wider TFT. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)